Glycogen Storage Disease Type IX in a 6-year-old Male: A Case Report - Shahab Noorian; Hossein Moravej; Zhila Afshar; Afagh Hassanzadeh Rad; Setila Dalili (Journal of Pediatrics Review)
Background: Glycogen storage diseases (GSDs) are a group of inherited metabolic disorders caused by enzyme deficiencies affecting glycogen synthesis or breakdown. Glycogen, stored mainly in the liver and muscles, is crucial for maintaining glucose levels during fasting or physical activity. GSDs lead to abnormal glycogen accumulation or impaired mobilization, causing symptoms, such as hypoglycemia, hepatomegaly, and muscle weakness. Each type of GSD results from a specific enzyme deficiency, requiring tailored management. Case Presentations: A case study of a 6-year-old boy with GSD type IX is presented, highlighting recurrent hypoglycemia, growth delay, and elevated liver enzymes. Genetic testing confirmed a PHKA2 mutation, and the patient’s management included frequent meals, cornstarch therapy, and regular liver function monitoring. The discussion emphasizes the importance of early diagnosis, genetic testing, and personalized treatment in managing GSDs. Conclusions: Future therapies, such as gene therapy and enzyme replacement, aim to address the root causes of GSDs rather than merely managing symptoms. Family education on hypoglycemia recognition and dietary restrictions is crucial for improving patient outcomes. Ongoing research into the molecular mechanisms of GSDs offers hope for more effective treatments, especially for GSD type IX, where individualized care can prevent complications like liver cirrhosis and promote better quality of life.